Exfoliated Graphite: A Surface Renewed Electrode for Environmental Applications - Idris, Azeez Olayiwola; Orimolade, Benjamin O.; Potlako, Mafa; Feleni, Usisipho; Nkambule, Thabo T. I.; Mamba, Bhekie B. (Frontiers in Sensors, 2022)
Exfoliated graphite is a 2D carbon material that has recently received great attention owing to its remarkable analytical merits such as fast electron migration, ease of surface regeneration, high-temperature resistance, ability to withstand high current density, excellent conductivity, and sensitivity. Due to its excellent analytical signature, exfoliated graphite electrode has been reportedly used in the construction of sensors and biosensors for various applications. This electrode can be used alone or blended with several nanomaterials/semiconductors for the degradation of various organic pollutants in wastewater. Despite the outstanding results reported in the use of exfoliated graphite electrode for various analytical applications, very few reports were documented in the literature. Therefore, this review elaborated on the importance of exfoliated graphite electrode for electrochemical analysis.